Analisis Filosufis Pemikiran Ibnu Miskawaih (Sketsa Biografi, Konsep Pemikiran Pendidikan, Dan Relevansinya Di Era Modern) - Ahmad Wahyu Hidayat; Ulfa Kesuma (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
This study aims to determine the philosophical analysis of Ibn Miskawaih thoughts (biographical sketches, concepts of educational thought, and their relevance in the modern era). Education is an effort made by someone to make a change towards a better one. In Indonesia education is more interpreted as a formal institution that has the aim to develop the academic potential of students in order to realize educational goals. One of the leaders of Islamic education, Ibn Miskawaih. Ibn Miskawaih is one of the leaders of Islamic education who contributed ideas to education. The focus of this study on the philosophical analysis of Ibn Miskawaih's thoughts (biographical sketches, concepts of educational thought, and their relevance to modern diera). This study uses the method of literature and analytical studies to build a theoretical framework in this article. In conclusion, Ibn Maskawaih considered the significance of education and the environment for humans in relation to moral formation. Thus human beings with their minds can choose and distinguish which ones should be done and which ones should be left behind. Ibn Maskawaih's thinking in education cannot be separated from his concept of man and morals. Ibn Maskawaih views human beings as having three powers, from those three types of power which are two from the material element and one from the spirit of God.